« Je comprends pas pourquoi on est obligé de se battre de même » : quand le processus judiciarisé de réparation des lésions professionnelles induit la précarité - Maxine Visotzky-Charlebois (Perspectives Interdisciplinaires sur le Travail et la Santé)
This paper discusses the results of a study that focuses on the human and financial costs of justice for those who are injured at or made ill by work. The results presented here are based on a qualitative field study which began in September 2018. Three elements that arose from the appeal process are discussed in light of the tangible and intangible costs of justice: the medicalization of the process and the delays and complexity of the judicial process. These elements are likely to influence the costs incurred by injured workers and pose specific challenges, particularly in terms of the quest for a medical expert and access to expert legal support. We end this paper with a discussion that highlights how the appeal process itself can be conceived as an additional layer of vulnerability that ultimately creates a form of precariousness.